The Influence of The Relationship Between Board of Commissioners, Board of Directors, and Risk Management on The Company Performance - Febianingsih, Putri Nilasari; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to confirm the theory and empirically prove the influence of the board of commissioners, board of directors, and risk management on the company's performance. The population in this study is banking companies registered with the Financial Services Authority (OJK) in 2021-2023 and who report a complete report on the implementation of Good Corporate Governance GCG in the annual report for the 2021-2023 period. This study uses a purposive sampling technique taken from ojk.go.id websites and websites of each bank, so that 14 banking companies, both conventional and Islamic banking, in Indonesia were obtained and 42 data were obtained as samples. This study uses multiple regression analysis using SPSS version 25. The results of the study show that the board of commissioners, the board of directors and risk management have no effect on the company's performance.